Placing Spirituality in the Contemporary World: The Islamic Spirituality Vs. Secularized Spirituality: Meletakkan Kerohanian dalam Dunia Kontemporari: Kerohanian Islam Vs. Kerohanian Sekular - Abdullah, Fatimah (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
This article argues that secular humanists’ scholars like postmodernists are developing great interest in spirituality as though they are beginning to have a positive approach towards religion and as though they are beginning to abandon their secular humanistic beliefs. Despite such positive approach towards spiritualism, they have not changed their position against religion. In fact, in the spiritual practices of Eastern religions such as the transcendental meditation of Buddhism and Hinduism in healing Western troubled souls has however no clear relationship with religiosity. In the same vein, Postmodern preaches that mental growth, development, inner peace and contentment are gained on a personal and individual level instead of developing a relationship with God. This kind of secularization to spirituality is absurd and confusing to Muslims who do not differentiate between the Western conceptions of spirituality and religiosity. Hence, the objective of this paper is to address the issue of spirituality brought forth by secular humanism and postmodern, by drawing the distinction between western secular conception of spirituality and Islamic spirituality, the nature and the significant of spirituality and the relationship between spirituality and religiosity and spiritual intelligence. This paper concludes there is a necessary and positive relationship between religious and spiritual practices and psycho-spiritual wellbeing and life as a whole. From Islamic perspective, no spirituality without religiosity. Spirituality is the essence of religiosity and they are undoubtedly of equal important and significant to understand the role of religion which is revealed from God, as a way of life. Hence, there is no good without God. Abstrak Artikel ini berhujah bahawa sarjana humanis sekular seperti postmodernis sedang mengembangkan minat yang besar dalam kerohanian seolah-olah mereka mula mempunyai pendekatan positif terhadap agama dan seolah-olah mereka mula meninggalkan kepercayaan humanistik sekular mereka. Walaupun pendekatan positif terhadap kerohanian, mereka tidak mengubah pendirian mereka terhadap agama. Malah, dalam amalan kerohanian agama-agama Timur seperti meditasi transendental agama Buddha dan Hindu dalam menyembuhkan jiwa-jiwa bermasalah Barat bagaimanapun tidak mempunyai hubungan yang jelas dengan religiositi. Dalam nada yang sama, Postmodern mendakwa bahawa pertumbuhan mental, perkembangan, kedamaian dalaman dan kepuasan diperoleh pada peringkat peribadi dan individu dan bukannya membina hubungan dengan Tuhan. Sekularisasi kepada kerohanian semacam ini adalah tidak masuk akal dan mengelirukan umat Islam yang tidak membezakan antara konsep kerohanian dan religiusiti dari percepsi Barat. Oleh itu, objektif artikel ini adalah untuk menangani isu kerohanian yang dibawa oleh humanisme sekular dan pascamoden, dengan membezakan antara konsep kerohanian sekular barat dan kerohanian Islam, sifat dan signifikan kerohanian dan hubungan antara kerohanian dan keagamaan. dan kecerdasan rohani. Artikel ini menyimpulkan terdapat hubungan yang perlu dan positif antara amalan keagamaan dan kerohanian serta kesejahteraan psiko-rohani dan kehidupan secara keseluruhan. Dari perspektif Islam, tiada kerohanian tanpa religiositi. Kerohanian adalah intipati religiositi dan mereka tidak dapat dinafikan sama penting dan signifikan untuk memahami peranan agama yang diturunkan daripada Tuhan, sebagai cara hidup. Oleh itu, tanpa agama dan wahyu dari Tuhan tidak akan ada kebaikan/salvation.